THE IMAGE OF A "TERRY EGOIST" IN THE PLAY BY EVGENY GRISHKOVETS "THE CITY" - Alexandra Valeryevna Ekabsons (Galaxy International Interdisciplinary Research Journal, 2024)
The article discusses the structure and method of creating the image of a "terry egoist". The definition of the modern understanding of a remark as a plot-forming element, the transition of a remark from the category of a service function to the category of a compositional device is given. Special attention should be paid to the remarks of "silence": pause remarks, extended remarks of "silence" ("silent", "she is silent", "a short pause", "father is silent", "he stands silently nodding his head", "trying to say something") and the dots scattered in the narration of the text in huge numbers.